Research of Characteristics of Families Raising Children with ASD - S.A. Morozov; S.G. Chigrina (Moscow State University of Psychology and Education, 2022)
The article considers results of the questionnaire of 629 families from 43 regions of Russia and the Republic of Belarus in terms of family composition, education and employment of parents. 76.5% of respondents' families are nuclear type. It is shown that with a high secondary level of education (76.3% higher level, 18.8% second ary special level) there is a low percentage of employment (40.5%). The range of distribution by profession dif fers by major occupational groups from the national average range. Revealed that among respondents16.7% are psychoeducational professionals (an average of 1.7% in the Russian Federation), accountants, economists, bank employees 14.7% (an excess of about 10 times from the national average), medical workers 6.6% (an excess of 3 times from the national average), employees in the field of information technology 3.0% (an excess of 2.5 times from the national average). The reasons of distortion of professions profile among respondents are considered. The demographic depression of families with children with autism (1.8 children per family) was revealed. The main directions for improving the situation are the development of the system of support of individuals with ASD, the organization of parental education in the field of autism, and socioeconomic assistance to the families of children with ASD.